The Role of Health, Safety, and Environment (HSE) in Mediating the Effect of Safety Behaviour and Dangerous Goods Handling Competency on Operational Performance at Palaran Fuel Terminal Samarinda - Agus Sulistiyono; Eduard Alfian Syamsya Sijabat; Reni Dian Octaviani; Aisyah Rahmawati; Sarinah Sihombing (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
The oil and gas industry is characterized by a high level of safety risk, particularly in activities involving the handling of fuel products classified as Dangerous goods (DG). Operational performance in high-risk work environments is strongly influenced by safety behaviour, technical competence, and the effectiveness of the Health, Safety, and Environment (HSE) system. This study aims to analyze the effect of safety behaviour and Dangerous goods handling competence on operational performance, with HSE as a mediating variable. This research adopts a quantitative approach using a survey method involving 188 respondents engaged in operational activities. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that safety behaviour and Dangerous goods handling competence have a positive and significant effect on operational performance. In addition, safety behaviour and DG competence significantly influence HSE. HSE is proven to have a positive effect on operational performance and acts as a mediating variable, mediating the relationship between safety behaviour and operational performance, and more strongly mediating the relationship between DG competence and operational performance. These findings confirm that improving operational performance requires an integrated approach combining safety behaviour, technical competence, and an effective HSE system. This study is expected to contribute both theoretically and practically to the management of safety and operational performance in high-risk industries.